2019
DOI: 10.1111/codi.14637
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on a train‐the‐trainer curriculum for robotic colorectal surgery

Abstract: Aim Robotic techniques are being increasingly used in colorectal surgery. There is, however, a lack of training opportunities and structured training programmes. Robotic surgery has specific problems and challenges for trainers and trainees. Ergonomics, specific skills and user–machine interfaces are different from those in traditional laparoscopic surgery. The aim of this study was to establish expert consensus on the requirements for a robotic train‐the‐trainer curriculum amongst robotic surgeons and trainer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…While early efforts were mostly focused on how to safely teach robotic pancreatic surgery in the context of highly specialized institutions, 91,92 there is now a compelling need to teach RPRs on a larger scale. Teaching a new surgical technique starts with the definition of who could be a teacher and where the newer procedures could be taught 93 . Although this aspect has not been specifically addressed in the literature, it is clear that accredited training centers should have a busy surgical activity in order to expose trainees to all cultural and technical aspects of RPRs 85 .…”
Section: Discussionmentioning
confidence: 99%
“…While early efforts were mostly focused on how to safely teach robotic pancreatic surgery in the context of highly specialized institutions, 91,92 there is now a compelling need to teach RPRs on a larger scale. Teaching a new surgical technique starts with the definition of who could be a teacher and where the newer procedures could be taught 93 . Although this aspect has not been specifically addressed in the literature, it is clear that accredited training centers should have a busy surgical activity in order to expose trainees to all cultural and technical aspects of RPRs 85 .…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings verändert der Einsatz komplexer Technologie im Operationssaal das chirurgische Vorgehen sowohl im Hinblick auf das operative Vorgehen, als auch die Interaktion der Mitarbeiter. Dies bedarf spezifischer Trainingskonzepte, um den Einsatz der Roboter sicher und effizient zu gestalten [ 5 , 6 ].…”
Section: Hintergrundunclassified
“…Whilst the evidence for the efficacy of robotic colorectal surgery has continued to evolve [1][2][3][4][5], the adoption of robotic surgery for colorectal resections has rapidly increased [6]. Although there are similarities with laparoscopic surgery, robotic surgery has certain training challenges due to the specific skills, ergonomics, interactions between team members and user-machine interfaces that are different from laparoscopic surgery [7]. Despite this rapid increase in robotic colorectal surgery, there is a lack of structured training programmes and concern that unregulated adoption of novel surgical techniques and technology may result in poor outcomes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The English National Training Programme in Laparoscopic Colorectal Surgery (LapCo) demonstrated that structured TTT courses had a significant impact on the quality of training delivered [19,20]. A European consensus on a TTT curriculum for robotic colorectal surgery concluded that there was a need for a TTT in robotic colorectal surgery course [7].…”
Section: Introductionmentioning
confidence: 99%